Factores de riesgos que causan el virus de inmunodeficiencia felina en gatos domésticos - Sornoza Aguirre, Ramon Alfredo (2019)
SUMMARY The virus of the immunodeficiency is a disease pathogen caused by the infections and the worry by the felines. This disease produces in cats, death, which does not have the cure, but it is about giving a treatment to the animal so that it can have a better quality of life, since this disease is not contagious for the human being. For this reason it is recommended to carry out a control of the animals with immunostimulants as the measure of the support of the virus affected with this virus. Key words: retroviruses, immunostimulants, pathogens.